2018
DOI: 10.1103/physrevb.98.024513
|View full text |Cite
|
Sign up to set email alerts
|

Filled skutterudite superconductor CaOs4P12 prepared by high-pressure synthesis

Abstract: In this paper, we report the transport, thermodynamic, and superconducting properties of a new filled skutterudite CaOs4P12 synthesized under high pressure and high temperature. The electrical resistivity of 3.4-4.8 mΩcm, carrier concentration of 3.8-6.1 × 10 20 cm −3 , and positive Hall coefficient suggest that CaOs4P12 is a semimetal with hole carriers. An anomaly due to low-energy optical modes corresponding to an Einstein temperature of 150 K was observed in the specific heat. Resistivity, dc magnetic susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Finally, it is worth to mention that the isostructural compound SrOs 4 As 12 is a superconductor with a T c of 4.8 K [21]. Quite recently a similar compound with the same structure, CaOs 4 P 12 , has been suggested to be a BCS-type superconductor with T c = 2.5 K [15]. It would be very interesting to perform NMR and NQR measurements on SrOs 4 As 12 and CaOs 4 P 12 for investigating their magnetic fluctuations, as well as superconducting properties, from a microscopic point of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth to mention that the isostructural compound SrOs 4 As 12 is a superconductor with a T c of 4.8 K [21]. Quite recently a similar compound with the same structure, CaOs 4 P 12 , has been suggested to be a BCS-type superconductor with T c = 2.5 K [15]. It would be very interesting to perform NMR and NQR measurements on SrOs 4 As 12 and CaOs 4 P 12 for investigating their magnetic fluctuations, as well as superconducting properties, from a microscopic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The compound crystallizes in a body-centered cubic structure with the space group Im3, and is now known to have a wide variety of compounds with the general formula AT 4 X 12 (A = alkali metal, alkaline earth metal, lanthanide, and actinide; T = Fe, Ru, Os, Co, Rh, Ir, and Pt; X = P, As, Sb, and Ge). These compounds have received much attention since they exhibit rich physical properties that include superconductivity, metal-insulator transition, ferromagnetism, antiferromagnetism, hybridization gaps (Kondo insulator behavior), nonfermi-liquid behavior, quadrupolar ordering, and field-induced heavy-fermion states [2][3][4][5][6][7][8][9][10][11][12][13][14][15], as well as excellent thermoelectric properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…The value of 2∆(0)/k B T c is estimated to be 2.5 using the on-set T c of 4.8 K. This value is slightly smaller than that of the BCS weak-coupling limit 2∆(0)/k B T c = 3.53. It should be noted that the isostructural compound CaOs 4 P 12 , has been suggested to be a BCS-type superconductor with T c = 2.5 K [58]. In order to discuss the superconducting properties of SrOs 4 As 12 in detail, one needs good quality samples with much smaller distribution of T c and the detailed study of the superconducting properties of SrOs 4 As 12 is a future project.…”
Section: B Superconducting Statementioning
confidence: 99%
“…For the semi-metal-filled skutterudite CaOs 4 P 12 with hole carriers, its resistivity, DC susceptibility and specific heat measurements show that its superconducting transition temperature T c is less than 2.5 K. Regarding the thermoelectric coefficient, the measured value 1.4 is consistent with the BCS theoretically predicted value of 1.43, which means that CaOs 4 P 12 is thus classified as a BCS-type weakly-coupled type-II superconductor. 41 In addition to the hardness of conventional insulating hard materials, the covalent metal TaB's temperature-dependent resistivity measurement demonstrates that the metal's electrical conductivity is close to that of a conductor, and turns into a superconductor when T = 7.8 K. 42 Cu 11 Bi 7 , another metastable material, was successfully synthesized under a pressure of 6 GPa and at a temperature of 800 K, and its superconducting transition temperature T c was measured as 1.36 K. According to the calculation result of density functional theory (DFT), it is shown that Cu 11 Bi 7 can exist stably under high temperature and high pressure conditions. Although both Cu 11 Bi 7 and CuBi belong to the high-pressure phase, DFT theory can correctly predict that the stable pressure of CuBi is lower than the stable pressure of Cu 11 Bi 7 , and successfully explains the orderly Cu "voids".…”
Section: Superconductor Materialsmentioning
confidence: 99%